Cystic Fibrosis: Recent Insights into Inhaled Antibiotic Treatment and Future Perspectives - Giovanni Taccetti; Michela Francalanci; Giovanna Pizzamiglio; Barbara Messore; Vincenzo Carnovale; Giuseppe Cimino; Marco Cipolli (MDPI AG, 2021)
Although new inhaled antibiotics have profoundly improved respiratory diseases in cystic fibrosis (CF) patients, lung infections are still the leading cause of death. Inhaled antibiotics, i.e., colistin, tobramycin, aztreonam lysine and levofloxacin, are used as maintenance treatment for CF patients after the development of chronic Pseudomonas aeruginosa (P. aeruginosa) infection. Their use offers advantages over systemic therapy since a relatively high concentration of the drug is delivered directly to the lung, thus, enhancing the pharmacokinetic/pharmacodynamic parameters and decreasing toxicity. Notably, alternating treatment with inhaled antibiotics represents an important strategy for improving patient outcomes. The prevalence of CF patients receiving continuous inhaled antibiotic regimens with different combinations of the anti-P. aeruginosa antibiotic class has been increasing over time. Moreover, these antimicrobial agents are also used for preventing acute pulmonary exacerbations in CF. In this review, the efficacy and safety of the currently available inhaled antibiotics for lung infection treatment in CF patients are discussed, with a particular focus on strategies for eradicating P. aeruginosa and other pathogens. Moreover, the effects of long-term inhaled antibiotic therapy for chronic P. aeruginosa infection and for the prevention of pulmonary exacerbations is reviewed. Finally, how the mucus environment and microbial community richness can influence the efficacy of aerosolized antimicrobial agents is discussed.